The role of the cooperative agricultural bank in agricultural activities after 2008: the role and impact in light of national initiatives - Dr.Mustafa Kamil Rasheed; Ali Shather Resen (Genius Journals, 2022)
After the year 2008, the Cooperative Agricultural Bank witnessed several ways of granting agricultural financing, which is the agricultural initiative, which includes seven specialized lending funds and the initiative of the Central Bank, in addition to agricultural loans from its own resources (short and long-term), where the highest amount granted through agricultural financing (958731). million dinars in 2012 with a contribution rate of (15.93%), while the lowest amount granted through agricultural financing amounted to (60923) million dinars and a contribution rate of (0.78%) in 2019.
Keywords: amounted; Cooperative; Bank; initiative